Tc17 CD8+ T cells accumulate in murine atherosclerotic lesions, but do not contribute to early atherosclerosis development. Issue 14 (16th October 2020) - van Duijn, Janine; de Jong, Maaike J M; Benne, Naomi; Leboux, Romain J T; van Ooijen, Marieke E; Kruit, Nicky; Foks, Amanda C; Jiskoot, Wim; Bot, Ilze; Kuiper, Johan; Slütter, Bram
Abstract: Aims: CD8 + T cells can differentiate into subpopulations that are characterized by a specific cytokine profile, such as the Tc17 population that produces interleukin-17. The role of this CD8 + T-cell subset in atherosclerosis remains elusive. In this study, we therefore investigated the contribution of Tc17 cells to the development of atherosclerosis. Methods and results: Flow cytometry analysis of atherosclerotic lesions from apolipoprotein E-deficient mice revealed a pronounced increase in RORγt + CD8 + T cells compared to the spleen, indicating a lesion-specific increase in Tc17 cells. To study whether and how the Tc17 subset affects atherosclerosis, we performed an adoptive transfer of Tc17 cells or undifferentiated Tc0 cells into CD8 −/− low-density lipoprotein receptor-deficient mice fed a Western-type diet. Using flow cytometry, we showed that Tc17 cells retained a high level of interleukin-17A production in vivo . Moreover, Tc17 cells produced lower levels of interferon-γ than their Tc0 counterparts. Analysis of the aortic root revealed that the transfer of Tc17 cells did not increase atherosclerotic lesion size, in contrast to Tc0-treated mice. Conclusion: These findings demonstrate a lesion-localized increase in Tc17 cells in an atherosclerotic mouse model. Tc17 cells appeared to be non-atherogenic, in contrast to their Tc0 counterpart. Graphical Abstract: